1990
DOI: 10.1093/intimm/2.9.885
|View full text |Cite
|
Sign up to set email alerts
|

Direct evidence for a functional role of HLA-DRB1 and-DRB3 gene products in the recognition of Dermatophagoides spp.(house dust mite) by helper T lymphocytes

Abstract: The contribution of the HLA-DRB1, -B3, and -B5 gene products in the recognition of Dermatophagoides spp. (house dust mite) by helper T cells isolated from an atopic individual (HLA-DRw12, DR7; DRw52b) with perennial rhinitis was investigated. Using a panel of histocompatible and histoincompatible accessory cells, the restriction specificity obtained for a long term T cell suggested that a component of the dust mite reactive repertoire recognized antigen in association with DRB3 gene products. Oligonucleotide D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
2

Year Published

1991
1991
2007
2007

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 29 publications
2
23
0
2
Order By: Relevance
“…It is not clear whether the dominance of clones reactive to peptides 46-65 and 106-125 is due to a relatively high affinity association of these peptides for HLA-DR2/5 or that precursor frequencies of the clones exist at higher levels in these ABPA patients due to a number of yet unidentified host determined genetic factors. Similar HLA-DR2 and DR5 restricted allergic responses to house dust mite and ragweed antigen have been reported (24)(25)(26)(27). In addition, genetic epidemiological studies and molecular analysis of HLA class II also support a strong association between DR2 and DR5 antigens and allergic responses to ragweed and grass pollen (28)(29)(30).…”
Section: Discussionsupporting
confidence: 66%
“…It is not clear whether the dominance of clones reactive to peptides 46-65 and 106-125 is due to a relatively high affinity association of these peptides for HLA-DR2/5 or that precursor frequencies of the clones exist at higher levels in these ABPA patients due to a number of yet unidentified host determined genetic factors. Similar HLA-DR2 and DR5 restricted allergic responses to house dust mite and ragweed antigen have been reported (24)(25)(26)(27). In addition, genetic epidemiological studies and molecular analysis of HLA class II also support a strong association between DR2 and DR5 antigens and allergic responses to ragweed and grass pollen (28)(29)(30).…”
Section: Discussionsupporting
confidence: 66%
“…Several epitopes derived from both the group I and II major allergens are known to be recognized by "disease-associated" T cells, namely, those that produce high levels of IL-4 and support the production of HDM-specific IgE. It has also been demonstrated that HLA-DRB1, -3, -4, and -5 gene products and DP class II molecules may restrict recognition of HDMderived T-cell determinants (31).…”
Section: Resultsmentioning
confidence: 99%
“…Recent genetic epidemiological studies analysing IgE antibodies specific for individual proteins of HDM initially suggested that HLA-DP class TI molecules contribute to the IgE response of HDM atopic individuals, but now the association is less clear [34]. However, investigation of the restriction specificity of HDM reactive T-cells isolated from atopic individuals demonstrates the broad heterogeneity of HLA class I1 molecules capable of presenting HDM derived peptides [19,20,35 Multiple HLA class I1 specificities also appear to function as restriction elements in recognition of Der p 2 by T-cells. The extent of the heterogeneity is demonstrated by the analysis of a panel of Der p 2 specific T-cell clones all isolated from the same HDM allergic individual.…”
Section: Hla Class 11 Restricted T-cell Recognition Of Hdm Allergensmentioning
confidence: 99%
“…The T-cell epitopes, either alone or in the presence of APC, are able to induce antigen specific non-responsiveness by presentation of the peptides complexed with MHC class I1 molecules on the surface of the human T-cells in the absence ofcostimulatory activity. Although major HDM determinants are recognized in association with HLA-DR, -DP or -DQ gene products [19,20,21,35], T-cells using each of these restriction elements may be anergized [21,42]. This system was initially described for tolerance induction using a peptide derived from the carboxyl terminus of influenza haemagglutinin in influenza-virus immune human T-cells [46].…”
Section: Functional Inuctication Qf Hdm-reactiiie T-cellsmentioning
confidence: 99%